RELEVANCE AND LINGUISTIC ACCURACY OF THE INFORMATION PROVIDED ON WEBSITES - Neringa Lekandrė; Gemma Navickienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The number of individuals or organisations providing textual information on their websites (both in native and foreign languages) is continuously increasing, which raises the issue of its quality. The research aims to investigate the relevance and linguistic accuracy of the information provided on business websites. The objectives are to theoretically define the notions of the relevance and linguistic accuracy of the information provided within the scope of Internet linguistics; identify the relevance and linguistic accuracy of the information found on the websites of translation agencies, and submit recommendations for corrections. The methods applied include a review of the theoretical sources on the relevance and linguistic accuracy of the information provided online, the descriptive analysis of the relevance and linguistic accuracy of the information found on business websites and modelling the improved versions of the content provided on the websites under investigation. The study revealed that the relevance of the website content depends on the target audience, market share, size of the company, the available layout options, and the scope of information. The information and description of services vary in quality. Even though most of the information provided on the websites selected is relevant and linguistically correct, the semantic, grammatical, and stylistic errors found on the homepages make an unfavourable impression. Some texts seem to have been machine-translated. Therefore, an assumption can be made that companies are reluctant to pay language service providers to create the content of their websites, and the internal human resources managing the websites are not aware of the requirements to be followed to maintain the relevance and linguistic accuracy of the information to be provided in several languages in case the company operates internationally. To avoid the most common pitfalls, more effort should be invested in delivering relevant and linguistically accurate information online; automated translation tools should not be used if there are no human resources available to check for errors; spelling and grammar checking applications and writing assistants should be applied.